Surface engineering to modulate human mesenchymal stem cell behavior - Wu, Yew Seng. (2010)
Surface micro-fabrication techniques have been widely used for spatial control of cells in culture and various types of biomolecules were immobilized onto the substrate to promote or resist cell attachment to surface. Through this technique (micropatterning), it is possible to fix cells onto targeted locations and arrays separated by a defined distance thus dictating their shape which influence commitment of stem cells to their different specifics lineage. In this project, responses of bone marrow human derived stem cells (hMSCs) were modulated via surface engineering techniques. In the first stage of the study, 5 extracellular matrixes (ECMs) and 1 attachment factor (AF) were screened for their suitability as the “ink” for printing of micropattern islands onto the substrate. Gene expression study showed that the non bias fibronectin is the best candidate for micropatterning as its effects on target gene expression did not vary much from the control. Furthermore, the study also revealed trends of those ECMs and AF where collagen was identified to be a suitable candidate for up-regulating osteogenic genes, gelatin for myogenic genes and laminin for neurogenic genes and osteogenic genes. In the second phase of the study, techniques for casting of PDMS elastomeric stamps and micro contact printing of fibronectin micropattern islands onto poly lactide-co-glycolide (PLGA) scaffold were established. Different cytoskeleton organization between cell immobilized on different fibronectin micropattern islands and unpatterned control were also observed. The optimized protocol coupled with the observed modulation in cytoskeletal re-arrangement of hMSCs on the designed micropatterns makes it a powerful tool to direct stem cells fates on a biodegradable scaffold.